Glucocorticoid receptor expression in human bronchial epithelial cells: effects of smoking and COPD - M. M. Verheggen; P. W. C. Adriaansen-Soeting; C. A. Berrevoets; P. Th. W. van Hal; A. O. Brinkmann; H. C. Hoogsteden; M. A. Versnel (Mediators of Inflammation)
Previously, we found that inflammatory mediators modulated the number and binding affinity of glucocorticoid receptors (GR) in human bronchial epithelial cell lines . In this study we investigated whether smoking and chronic obstructive pulmonary disease (COPD), both characterized by airway inflammation with increased levels of inflammatory mediators , affect GR characteristics in cultured human bronchial epithelial cells (HBEC). A statisticallys ignificant difference was found be tween the dissociation constant (Kd) values in HBEC from smoking (Kd = 0.98 ± 0.08 nM; n=6) and nonsmoking controls (Kd = 0.76 ± 0.10 nM, p=0.03; n=5), but no significant difference was found between the mean number of binding sites . Our results are the first indication that cultured HBEC from smokers possess GR with a lower binding affinity. This may result from the in flammation found in the airways from smokers . Further more, these results provide furthere vidence that the bronchial epithelium may be an actual target for inhaled glucocor ticoid therapy.